2017
DOI: 10.1007/s10815-017-1087-z
|View full text |Cite
|
Sign up to set email alerts
|

Superovulation alters DNA methyltransferase protein expression in mouse oocytes and early embryos

Abstract: This study has demonstrated for the first time that superovulation alters expression levels of the DNMT proteins, a finding that indicates that certain developmental defects in superovulated oocytes and early embryos may result from impaired DNA methylation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 44 publications
5
37
0
4
Order By: Relevance
“…Indeed, some studies have reported increased epigenetic anomalies in children born after assisted reproductive technologies (ARTs; Lawrence, 2008) and that the overgrowth found in calves and lambs born after these technologies uses could be caused by methylations fails (Sinclair, Young, Wilmut, & McEvoy, ; Young et al, ). ARTs commonly use superovulation protocols that decreased DNMTs protein expression in oocytes (Uysal, Ozturk, & Akkoyunlu, ). Oocyte imprints seems to be established in later oocyte development stages (Lucifero, Mertineit, Clarke, Bestor, & Trasler, ; Obata & Kono, ; Obata et al, ; Tada et al, ) which could be linked with the higher expression previous found of these three DNMTs in mouse (Uysal, Ozturk, & Akkoyunlu, ) and bovine oocytes (O'Doherty, O'Shea, & Fair, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies have reported increased epigenetic anomalies in children born after assisted reproductive technologies (ARTs; Lawrence, 2008) and that the overgrowth found in calves and lambs born after these technologies uses could be caused by methylations fails (Sinclair, Young, Wilmut, & McEvoy, ; Young et al, ). ARTs commonly use superovulation protocols that decreased DNMTs protein expression in oocytes (Uysal, Ozturk, & Akkoyunlu, ). Oocyte imprints seems to be established in later oocyte development stages (Lucifero, Mertineit, Clarke, Bestor, & Trasler, ; Obata & Kono, ; Obata et al, ; Tada et al, ) which could be linked with the higher expression previous found of these three DNMTs in mouse (Uysal, Ozturk, & Akkoyunlu, ) and bovine oocytes (O'Doherty, O'Shea, & Fair, ).…”
Section: Discussionmentioning
confidence: 99%
“…T A B L E 5 Total cell numbers and their allocation to the ICM and TE lineages of yak blastocysts from the optimum concentration FGF10 groups (5.0 ng/ml). Ohnami et al 2012;Uysal et al 2017aUysal et al , 2017b. However, the functions of these genes have been studied by various approaches, and the obtained results differ notably (Antalíková et al 2015 was significantly increased in the group treated with 5 ng/ml FGF10 during both IVM and capacitation (Table 5 and Figures 6 and 8).…”
Section: Discussionmentioning
confidence: 96%
“…DNA methylation is an important epigenetic mechanism and has been implicated in playing critical roles during gametogenesis, fertilization, and preimplantation embryo development, helping in the regulation of the expression of development-related genes and establishing maternal and paternal imprints in a timely manner (Bartolomei & Fergusonsmith, 2011;Tanigawa et al, 2008;Uysal, Ozturk, & Akkoyunlu, 2017a, 2017bD. Zhang et al, 2018).…”
mentioning
confidence: 99%
“…In ovarian superstimulation, various studies suggest that the acquisition of imprinting patterns in the oocyte might be perturbed and lead to abnormal allelic expression in later embryo and placenta development (reviewed in Anckaert et al, 2013;McGraw and Trasler, 2013). However, studies show that superovulation treatments do not alter normal imprinted methylation acquisition in oocytes, but rather disrupt maternal-effect gene products that are required during pre-implantation for imprint maintenance (Denomme et al, 2011;Uysal et al, 2018). We also showed that some of these induced errors of imprinted gene expression (H19, Igf2) present in mid-gestation mouse placenta are no longer apparent at the end of the gestation (Fortier et al, 2008;Fortier et al, 2014).…”
Section: Art Proceduresmentioning
confidence: 99%